Russian Phraseological Units with Zoonyms: Aspects of Comprehensive Description (A Case Study of Expressions Featuring Zoonym ‘volk’ [Wolf] - Quanming Wu; O. A. Gorban (Научный диалог)
This article presents a comprehensive analysis of the phraseological units ‘staryy volk’ [old wolf], ‘travlenyy volk’ [tricked wolf], ‘morskoy volk’ [sea wolf], ‘volkom vyt'’ [to howl like a wolf], and ‘khot' volkom voy’ [you might as well howl like a wolf], which reflect a significant image of the wolf in Russian culture. The aim of this study is to identify the interconnections among their systemiclinguistic, linguocultural, and functional characteristics. The relevance of the research is underscored by the necessity for a thorough description and explanation of the trends in the realization of the linguistic phraseological inventory in speech. The study is based on data from the Russian National Corpus. It is demonstrated that these phraseological units characterize individuals based on their personality traits and behaviors, express varying degrees of negative emotions, and exhibit diverse stylistic nuances and grammatical structures. The functioning of these idioms is influenced by their composition (the expression featuring the zoonym ‘travlenyy volk’ [tricked wolf] is rarely encountered and primarily appears in literary texts), their figurative components (the expression ‘morskoy volk’ [sea wolf] is the most frequent, losing its association with predation and reflecting a stereotypical image of a sailor), lexical meanings (in literary texts, nominal phraseological units often serve a predicative function when characterizing individuals), and stylistic properties (the expressiveness and colloquial nature of the unit ‘khot' volkom voy’ [you might as well howl like a wolf] predominantly determine its use in literary texts within character dialogue).